HUBUNGAN ANTARA FAKTOR LINGKUNGAN FISIK RUMAH DENGAN KEJADIAN PNEUMONIA PADA ANAK BALITA DI WILAYAH KERJA PUSKESMAS SEMIN I KABUPATEN GUNUNG KIDUL - Amalia Mustika Hayati; Suhartono Suhartono; Sri Winarni (Fakultas Kesehatan Masyarakat Universitas Diponegoro, 2017)
Infectious disease is one of the major health problems in Indonesia. The incidence of pneumonia in infants at the working area of Community Health Centre Semin is 9,1% cases. The purpose of this study was to analyze the association of environmental house factors with pneumonia incidence in children under five years at the working area of Community Health Centre Semin I GunungKidul District 2017. This study used observational analytic research with case control approach, discovered populations of infants in the group of some 126 cases and the control group as much as 1.710. The sample is selected by simple random sampling, with sample of 90 respondents which fulfill the criteria as research subject. The data analysis used were univariate and analytic bivariate using chi square statistic test with significance value ( = 5%) and univariate analysis showed 12.2% of respondents aged 26 years; 47.8% respondents with recent high school education; 62% as housewives; and 54.4% of income <UMR. The results were analyzed by chi square analysis of natural lighting (p = 0,000), humidity (p = 0,001), ventilation area (p = 1,000), wall type (p = 0,230), temperature (p = 0,833), occupancy density (p = 0,205 ), Fuel type (p = 0,271), presence of smoking family member (p = 0,121), and type of floor (p = 1,000). There is an association between natural lighting (p = 0,000; OR = 25.231) and humidity (p = 0.001; OR = 5,474) with the incidence of pneumonia in infants. There is no association between ventilation area, wall type, temperature, occupancy density, fuel type, existence of smoking family member, floor type with incidence of pneumonia in infants. Society needs to pay attention to physical condition and maintain air quality and natural light as always open the window in the morning and evening.